Optimizing E-learning and Blended learning: Implementation Strategies in Digital Education Transformation - Meriyati Meriyati; Nabila Al Najla; Nur Hasanah; Linggaria Lova; Muhammad Fajar; Agus Jatmiko; Chairul Amriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the optimization of e-learning and blended learning as implementative strategies in digital education transformation, focusing on forms of implementation, supporting and inhibiting factors, and their impact on learning effectiveness. This research employs a qualitative approach through a library study of recent scientific literature related to digital learning. The findings indicate that e-learning and blended learning significantly enhance flexibility, accessibility, interactivity, and students’ learning autonomy. However, the effectiveness of e-learning tends to be limited when it is not supported by adequate pedagogical interaction. In contrast, blended learning proves to be more effective as it proportionally integrates the strengths of online and face-to-face learning, resulting in a more adaptive and meaningful learning experience. The study also reveals that successful implementation is not solely determined by technology, but by the quality of instructional design and teachers’ digital competence. On the other hand, major challenges include limited infrastructure, low digital literacy, and the lack of integrated educational policies. Therefore, systematic implementative strategies are required through strengthening digital competencies, developing adaptive curricula, and providing sustainable policy support to achieve effective digital education transformation.